EVALUASI SISTEM PENGELOLAAN LIMBAH CAIR DI RUMAH SAKIT PARU SURABAYA - Elis Sugihartini; Ferry Kriswandana; Hadi Suryono (Poltekkes Kemenkes Surabaya, 2013)
Hospital activities could be potentially reduces the quality of the environment and publichealth, especially from the medical home activities. One of this activity produces liquid wastethat are harmful to the hospital environment and the surrounding community if the disposal isnot treated before discharge into the water streams, thus it is important to monitoring andhandling in the hospital environment.This research is a descriptive study with the aim to describe the existing condition ofthe Waste Management System on Pulmonary Hospital at Surabaya. This research is useful tothe Hospital in order to improve their tunnel and immediately running the IPAL to reduce thelevels of pollutants and becomes the safe environment.The results of this study showed that the effluent liquid waste on Pulmonary Hospital atSurabaya has not been in compliance with the State Environmental Ministerial Decree ofRepublic Indonesia No : MEP - 58/MENLH/XIII/1995 because in the results of laboratoryexaminations was conducted on May 11, 2013 as the parameters of BOD, COD, TSS, and MPN,the coli bacteria/100 obtain a percentage of 134 ml mg/I, 237 mg/I, 20 mg/I and 9 x 10-8MPN/100 ml which is not considered feasible due to exceeding quality standards for liquidwaste Constanta to be dispose in water streams. Problems that exist in pulmonary hospitalsnowadays is the liquid waste treatment system due to discharge of liquid waste generated fromvarious sources is not running yet and it does not meet the capacity of the existing IPAL,irregularities found in the existing management system in a pulmonary hospital Surabaya, afterinvestigators traced by researchers there are some pipelines that leak or loss of liquid wastethat directly flows in drainage tunnels, and the sump apparently are not water resistant, and itcaused the water seep or seep into the ground.It is advisable for the pulmonary hospital at Surabaya to improve the liquid wastesystems, from the source to the hospitals liquid waste treatment such as repairing tunnels andfixing the sump. And the most important thing is to immediately run the existing IPAL inpulmonary hospital Surabaya so that the disposal of liquid waste can be reducing the levels ofpollutants and does not pollute or adversely affects the hospital environment or the localcommunity.Keywords: Liquid waste management systems, hospital liquid waste,PENDAHULUANLatar BelakangHospital liquid waste impacts.